A Little Engine that Could ... Domestic Private Companies and Vietnam's Pressing Need for Wage Employment - Steer, Liesbet (The World Bank, 2002)
Vietnam's young private sector is growing fast, due mainly to a policy environment that recognizes the importance of private entrepreneurship—particularly to help increase significantly job creation, which the country needs urgently. To extend the benefits of private sector growth from the urban centers where it has so far been concentrated to the rural areas where most Vietnamese live—and where underemployment is heaviest—more information on what is working and what is not will be needed. Steer and Taussig present an objective picture of Vietnam's emerging private sector two years after the implementation of its much praised Enterprise Law. Private companies are significantly better off than they were a couple years earlier, when regional economic recession and stagnating domestic policy reforms had nearly halted development of the formal private sector. At the same time, the sector's small base means that its impressive rates of job creation still fall far short of matching the booming growth of the overall work force. Data for this paper were collected from Vietnam's General Office of Statistics, individual company case studies, and a national firm-level survey designed and implemented by the authors. The research reveals significant gaps in available private sector data and flaws in current data-gathering methodologies, calling into question the ability of policymakers and advisors to understand rapid, ongoing economic developments and make appropriate policy decisions. The paper also seeks to provide a starting point and an impetus for more targeted research aimed at identifying and addressing specific obstacles to sustainable and broad-based job and wealth creation.